The Millenial-Responsible Segment, as an Ideal Market Goal for Mayan Tourist Enterprises - Gatica-Santamaría , Angelina; Ocampo-Franco , Martha V.; Sánchez-Estrada , Diana (Ingenio y Conciencia Boletín Científico de la Escuela Superior Ciudad Sahagún, 2020)
The increasing purchasing power of the population sector denominated: Millenial, its capacity of influence, the tendency of its growth and styles of purchase; make this group of people, a segment of market pursued by the companies of products and services. This segment of the market, besides its high degree of interaction with electronic devices, shows interest in tourism products oriented towards sustainability. The plans and visions of tourism, both internationally and in Mexico, speak of the search for a new model of tourism development in line with market trends and also with the need for a more equitable wealth distribution system. The proposed diversification guides the tourism development of the state of Quintana Roo toward the exploration of ecotourism and rural alternatives in the region; Based on the existence of populations of Mayan origin. This work demonstrates the compatibility of destinations such as Maya Ka’án (launched as the new tourism brand of Quintana Roo) with the segment of the millenial-responsible traveler, since its attractions were conceptualized to receive a responsible tourist, lover of nature and culture that requires defining the opportunity of supply and the relationship between communities and the new profiles of travelers, including the responsible millennia